Energy Intensive Sectors of the Indian Economy : Path to Low Carbon Development - World Bank (World Bank, 2012)
The report is divided into seven chapters. Chapter one discusses India's current carbon footprint, the drivers that will contribute to growth in Green House Gas (GHG) emissions, the objectives of the study, and the scope and methodology of the analytical approach. Chapter two provides an overview of each of the sectors covered by the study, along with their respective specific challenges and past performance, and the modeling approach adopted in the study. Chapters three, four, and five provide the specific assumptions and findings of the three scenarios: (1) scenario one, alternatively called five year plans scenario, assumes full implementation of the five year plans and other projections and plans by the government of India; (2) scenario two, alternatively called delayed implementation, more closely follows historical performance in implementation of the five year plans; (3) scenario three, or all-out stretch scenario, adds to scenario one additional steps to increase energy efficiency and low-carbon energy sources Sensitivity analysis is conducted on each scenario. Chapter six provides a brief comparison of the results of the three scenarios, and chapter seven concludes with a brief description of the challenges of low-carbon development in India.